The Russian tragedy. Comprising: The Russian tragedy. The Russian revolution and the communist party. The Kronstadt rebellion. Comp. and introd.: by W.G. Nowlin Jr (Cienfuegos Press, 1976)
First publ. as three separate pamphlets in 1922 by Der Syndikalist, Berlin.